Pheochromocytoma with hypertensive crisis due to glucocorticoid administration: a case report and review of the literature - Taimur, SDM; Karim, MR; Rahman, MH; Gomes, HI; Salahuddin, M; Farzana, I; Fahmida, AS (Bangladesh Journal of Medical Science, 2011)
We report a patient who presented with single episode of severe hypertension after intramuscular injection of betamethasone which was given to treat acute exacerbation of bronchial asthma. Episode of severe arterial hypertension was associated with pulmonary edema, acute renal failure and hyperkalemia. Further evaluation by appropriate diagnostic tests revealed that the patient is a case of phaechoromocytoma. This neoplasm was excised successfully and the patient is presently asymptomatic.We believe that this episode was initiated by glucocorticoid injection. Key words: Betamethasone, glucocorticoids, hypertensivecrisis, pheochromocytoma. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8369 BJMS 2011; 10(3): 213-215